The Ecosystem of Ethical Decision Making: Key Drivers for Shaping the Corporate Ethical Character - Sartzetaki, Maria; Moutzouri, Antonia; Karagkouni, Aristi; Dimitriou, Dimitrios (Conatus - Journal of Philosophy, 2025)
In today’s global economy, large corporations possess considerable power and exert a profound impact on the societies and the environments in which they operate. The effectiveness of Corporate Social Responsibility initiatives can widely vary, depending on how well they align moral principles and social expectations, thus enhancing their impact on societal welfare and environmental sustainability. This paper examines the practical application of ethical theories in the corporate world, moving beyond normative prescriptions to what defines a corporation’s ethical character. The transition to applied ethics represents a shift towards actionable guidance and contextual relevance in a way that takes into account all the involved forces and the practical implications for various stakeholders. A conceptual framework is developed to depict the relationships and decision-making influences within a socio-economic system and outline an ethical zone where care and justice ethics converge, indicating that decisions are just and do not neglect the welfare of individual stakeholders, society and the environment.